Human Platelet Membrane Functionalized Microchips with Plasmonic Codes for Cancer Detection. (27th May 2019) - Kumar, Sumit; Han, Jae‐A; Michael, Issac J.; Ki, Dongyeob; Sunkara, Vijaya; Park, Juhee; Gautam, Shreedhar; Ha, Hong Koo; Zhang, Liangfang; Cho, Yoon‐Kyoung
Abstract: The possibility of functional roles played by platelets in close alliance with cancer cells has inspired the design of new biomimetic systems that exploit platelet–cancer cell interactions. Here, the role of platelets in cancer diagnostics is leveraged to design a microfluidic platform capable of detecting cancer‐derived extracellular vesicles (EVs) from ultrasmall volumes (1 µL) of human plasma samples. Further, the captured EVs are counted by direct optical coding of plasmonic nanoprobes modified with EV‐specific antibodies. Owing to the inherent properties of platelets for multifaceted interaction with cancer cells, the microfluidic chip equipped with a biologically interfaced platelet membrane‐cloaked surface (denoted "PLT‐Chip") can capture a significantly higher number of EVs from multiple types of cancer cell lines (prostate, lung, bladder, and breast) than the normal cell‐derived EVs. Furthermore, this chip allows the monitoring of the growth of tumor spheroids (100 µm–2.5 mm) and clearly distinguishes the plasma of cancer patients from that of normal healthy controls. This robust, multifaceted, and cancer‐specific binding affinity, coupled with excellent biocompatibility, is a unique feature of platelet membrane‐cloaked surfaces, which therefore represent promising alternatives to antibodies for application in EVs‐based cancer theranostics. Abstract : A biologically interfaced microchip consisting of a platelet membrane‐cloaked surface for cancer detection is reported. Owing to the variegated functions of proteins associated with human platelets, which bind a broad spectrum of cancer cell‐derived extracellular vesicles, the resulting microdevice accurately detects cancer from ultrasmall volumes of patient's plasma samples, with high sensitivity.